Identifying and Producing Effective Teachers - Seth Gershenson (Institute of Labor Economics (IZA), 2021)
Teachers are among the most important school-provided determinants of student success. Effective teachers improve students' test scores as well as their attendance, behavior, and earnings as adults. However, students do not enjoy equal access to effective teachers. This article reviews some of the key challenges associated with teacher policy confronted by school leaders and education policymakers, and how the tools of applied economics can help address those challenges. The first challenge is that identifying effective teachers is difficult. Economists use value-added models to estimate teacher effectiveness, which works well in certain circumstances, but should be just one piece of a multi-measure strategy for identifying effective teachers. We also discuss how different policies, incentives, school characteristics, and professional-development interventions can increase teacher effectiveness; this is important, as schools face the daunting challenge of hiring effective teachers, helping teachers to improve, and removing ineffective teachers from the classroom. Finally, we discuss the supply and mobility of teachers, including the consequences of teacher absenteeism, the distribution of initial teaching placements, and the characteristics and preferences of those who enter the profession.
Keywords: I24; I21; 330; teacher supply; teacher effectiveness; incentive pay; value-added models